Knowledge Based Sustainable Economic Development 2018
DOI: 10.31410/eraz.2018.868
|View full text |Cite
|
Sign up to set email alerts
|

Crowdfunding and social responsibility: creating economic value and social value

Abstract: This work begins with the study of the phenomena of crowdfunding, highlighting its importance as an alternative form of financing. In the crowdfunding world the dimension of the social impact that it can generate is increasing, supporting projects of high civic and moral value. Crowdfunding campaigns increasingly finance innovative projects focused on biotech and environmental sustainability. The focus of this work is the study of crowdfunding as a tool for best practices, capable of creating not only economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Over the last couple of years, B-corps have increased their use of crowdfunding platforms to finance social innovation and sustainability projects [40]. In this way, they can generate economic and social value [41]. Crowdfunding and crowdlending represent two critical components in the financing of innovative ideas to support social sustainability [24] and encompass return-on-investment expectancy, transparency obligations, integrity, and responsible governance to crowdlenders [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last couple of years, B-corps have increased their use of crowdfunding platforms to finance social innovation and sustainability projects [40]. In this way, they can generate economic and social value [41]. Crowdfunding and crowdlending represent two critical components in the financing of innovative ideas to support social sustainability [24] and encompass return-on-investment expectancy, transparency obligations, integrity, and responsible governance to crowdlenders [25].…”
Section: Discussionmentioning
confidence: 99%
“…This form of financing, together with crowdlending, enables companies to achieve social development and stakeholder engagement. Crowdfunding is mainly aimed at financing innovative sustainability projects [40], to create both economic and social value [41]. Several authors have demonstrated that [42] crowdfunding can be used in a variety of ways:…”
Section: Journal Of Business Researchmentioning
confidence: 99%